Prognostic validation of a new classification system for extent of resection in glioblastoma: A report of the RANO resect group - Karschnia, Philipp; Young, Jacob S.; Dono, Antonio; Häni, Levin; Sciortino, Tommaso; Bruno, Francesco; Juenger, Stephanie T.; Teske, Nico; Morshed, Ramin A.; Haddad, Alexander F.; Zhang, Yalan; Stoecklein, Sophia; et al. (Neuro-Oncology, 2023)
Background: Terminology to describe extent of resection in glioblastoma is inconsistent across clinical trials. A surgical classification system was previously proposed based upon residual contrast-enhancing (CE) tumor. We aimed to (1) explore the prognostic utility of the classification system and (2) define how much removed non-CE tumor translates into a survival benefit. Methods: The international RANO resect group retrospectively searched previously compiled databases from 7 neuro-oncological centers in the USA and Europe for patients with newly diagnosed glioblastoma per WHO 2021 classification. Clinical and volumetric information from pre-and postoperative MRI were collected. Results: We collected 1,008 patients with newly diagnosed IDHwt glioblastoma. 744 IDHwt glioblastomas were treated with radiochemotherapy per EORTC-26981/22981 (TMZ/RT→TMZ) following surgery. Among these homogenously treated patients, lower absolute residual tumor volumes (in cm3) were favorably associated with outcome: patients with "maximal CE resection"(class 2) had superior outcome compared to patients with "submaximal CE resection"(class 3) or "biopsy"(class 4). Extensive resection of non-CE tumor (≤5 cm3 residual non-CE tumor) was associated with better survival among patients with complete CE resection, thus defining class 1 ("supramaximal CE resection"). The prognostic value of the resection classes was retained on multivariate analysis when adjusting for molecular and clinical markers. Conclusions: The proposed "RANO categories for extent of resection in glioblastoma"are highly prognostic and may serve for stratification within clinical trials. Removal of non-CE tumor beyond the CE tumor borders may translate into additional survival benefit, providing a rationale to explicitly denominate such "supramaximal CE resection."
CRIS-Team Scopus Importer:2023-09-13
Keywords: classification; EOR; glioblastoma; outcome; surgical resection